Simplified or not Simplified? The Different Guises of Mediated English at the European Parliament - Ferraresi, Adriano; Bernardini, Silvia; Petrović, Maja; Lefer, Marie-Aude (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
In this article we describe a framework for the corpus-based comparative investigation of interpreting and translation, illustrating it through a study of simplification across different modes of language production and across different language pairs. We rely on EPTIC, a corpus featuring plenary speeches at the European Parliament in their interpreted and translated versions, aligned to each other and to their source texts in English<=>Italian and English<=>French. Aiming to shed light on lexical simplification in different mediation modes, we compare interpretations and translations to each other and to comparable original speeches and their edited written versions. Specifically, we compare lexical features (lexical density, type-token ratio, core vocabulary and list head coverage) in interpreting and translation into English from French and Italian, both in a monolingual comparable perspective and an intermodal perspective. Our results do not unconditionally support the simplification hypothesis: lexical simplification is observed in mediated English, but is found to be greater when the source language is French, and in interpretations rather than translations. We conclude that this feature is contingent on both the mediation mode and the source languages involved, and that the influence of the latter seems to be stronger than that of the former.